Structural equation modeling for social capital empowerment in supporting mangrove rehabilitation - I. Listiana; D. Ariyanto (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Improving welfare requires continuous and various efforts, including enhancing social capital and local institutions for the preservation of mangrove forests. Reinforcing local social and institutional capital to enhance mangrove ecosystems is crucial for understanding the intricate social systems necessary to conserve, manage, and restore mangrove ecosystem services. The purpose of this study is to determine the relationship between social capital and social institutions with the sustainability of mangrove rehabilitation in the Teluk Pandan and Padang Cermin districts of Lampung, Indonesia, in 2023.METHODS: This study analyzes the role of local social and institutional capital in the welfare of communities residing around mangrove forests in the Way Ratai district of Pesawaran Regency. This study employs a survey research approach, drawing samples from the population, and utilizes both quantitative and qualitative data analysis. A sample of 300 respondents was selected based on the guidelines for Structural Equation Model analysis. The study was carried out in two sub-districts of Pesawaran Regency. The districts were deliberately chosen due to the fact that they are designated mangrove forest rehabilitation areas. Data collection took place from July to December 2023. Data analysis involved tabulation techniques and Structural Equation Model analysis using Linear Structural Relations.FINDINGS: The findings suggest that social institutions, such as customary practices, sanctions, and conflict, have a negative impact on mangrove rehabilitation and welfare. Increasing the social capital of communities surrounding mangrove forests has a significant influence on mangrove rehabilitation and welfare, including the fulfillment of basic needs like shelter, food, access to healthcare, and education. Community leaders oversee activities, encourage community involvement in mangrove rehabilitation, and ensure the smooth running of government programs.CONCLUSION: Social capital can be enhanced through group meetings, social gatherings, initiatives to raise awareness about tourism, and mangrove conservation groups. The goal of empowerment is to create self-sufficient and socially empowered communities capable of meeting their physical, economic, and social needs. This fosters self-confidence and allows them to voice their aspirations, secure their livelihoods, engage in social endeavors, and face life independently. Social capital influences community participation in mangrove rehabilitation.